Elections and politicals parties. An approach to the balance of historiography in the Latin American context - Santos Hernández, Fabio (Universidad Pedagógica y Tecnológica de Colombia, 2012)
In Colombia, the creation of citizenship and nation have been closely linked, as in most of Latin America, to the Electoral Processes. These Processes has been studied from several historiographical trends, that is why this article seeks to revise those movements in order to consider them as basis when trying to write history of Political Parties. These trends are analyzed in order to observe the events that have marked the history of towns, cities and countries during the nation’s formation as well as its civil culture and democratic elections. Likewise, reviewing these historiographical trends enables us to visualize the Colombian bipartisanship which generates controversy, because despite a constant existence of more than one hundred ifty years, it is considered by some to be the constant confrontation between two political factions seeking to gain power.